Systematic evaluation of genetic mutations in ALS: a population-based study. Issue 11 (27th July 2022) - Grassano, Maurizio; Calvo, Andrea; Moglia, Cristina; Sbaiz, Luca; Brunetti, Maura; Barberis, Marco; Casale, Federico; Manera, Umberto; Vasta, Rosario; Canosa, Antonio; D'Alfonso, Sandra; Corrado, Lucia; et al.
Abstract : Background: A genetic diagnosis in Amyotrophic Lateral Sclerosis (ALS) can inform genetic counselling, prognosis and, in the light of incoming gene-targeted therapy, management. However, conventional genetic testing strategies are often costly and time-consuming. Objective: To evaluate the diagnostic yield and advantages of whole-genome sequencing (WGS) as a standard diagnostic genetic test for ALS. Methods: In this population-based cohort study, 1043 ALS patients from the Piemonte and Valle d'Aosta Register for ALS and 755 healthy individuals were screened by WGS for variants in 42 ALS-related genes and for repeated-expansions in C9orf72 and ATXN2. Results: A total of 279 ALS cases (26.9%) received a genetic diagnosis, namely 75.2% of patients with a family history of ALS and 21.5% of sporadic cases. The mutation rate among early-onset ALS patients was 43.9%, compared with 19.7% of late-onset patients. An additional 14.6% of the cohort carried a genetic factor that worsen prognosis. Conclusions: Our results suggest that, because of its high diagnostic yield and increasingly competitive costs, along with the possibility of retrospectively reassessing newly described genes, WGS should be considered as standard genetic testing for all ALS patients. Additionally, our results provide a detailed picture of the genetic basis of ALS in the general population.